Estudio comparativo de dos métodos químicos para la extracción de aceite de sacha inchi - Barrezueta Ramírez, Jessy Angela; Guzmán Chávez, Joyce Cristina (Machala: Universidad Técnica de Machala, 2023)
The use of ethyl acetate as an alternative to replace n-hexane in order to obtain of oil from Sacha Inchi seeds was evaluated; in this way, the oil was extracted from Sacha Inchi seed oil, previously ground, by organic solvents (ethyl acetate and n-hexane) was done with the assistance of ultrasound at a power of 40 HZ at room temperature (24 °C) for 30 minutes. The oil obtained from each treatment was characterized by Gas Chromatography coupled to Mass Spectrometry (GC-MS) using the TRWAX column (30 m long, 0.25 mm internal diameter, and 0.25 µm thick) for the analysis, identification and quantification of the profile of the fatty acids contained. It was found that sacha inchi oil contains six acids, including palmitic, stearic, oleic, elaidic, linoleic and linolenic acids. The values of saturated fatty acids (palmitic acid and stearic acid) were approximately 7%, while 0.6% of elaidic acid (trans-saturated acid), on average; the sample extracted with ethyl acetate (0.44%) had a lower content. High oleic acid (9.63%) and linoleic acid (33.55%), on average; with no significant difference between the use of n-hexane and ethyl acetate. Also, a high value of linolenic acid was obtained (49.10% average), which was higher in the sample extracted with ethyl acetate. In conclusion, ethyl acetate can replace hexane as a solvent in the extraction of Sacha Inchi seed oil and provide a lower environmental impact, improved safety, and better quality.
Se comparó el uso del acetato de etilo como alternativa para sustituir el n-hexano en la extracción del aceite de las semillas de sacha inchi; de este modo, se procedió con la extracción del aceite de las semillas de sacha inchi, previamente molidas, con la ayuda de solventes orgánicos (acetato de etilo y n-hexano) con asistencia de ultrasonido a una potencia de 40 HZ a temperatura ambiente (24 °C) por 30 minutos. El aceite obtenido de cada tratamiento fue caracterizado por Cromatografía de Gases acoplada a la espectrometría de masas (CG-MS) utilizando la columna TRWAX (30 m de longitud, 0.25 mm de diámetro interno y 0,25 µm de espesor) a través del análisis, identificación y cuantificación del perfil de los ácidos grasos presentes. Se obtuvo que el aceite de sacha inchi presenta seis ácidos grasos entre ellos el palmítico, esteárico, oleico, elaídico, linoleico y linolénico. Los valores de ácidos grasos saturados (ácido palmítico y ácido esteárico) fueron alrededor del 7%, mientras que, un 0,6% de ácido elaídico (ácido trans saturado), en promedio; siendo menor en la muestra extraída con acetato de etilo (0,44%). Alto contenido de ácido oleico (9,63%) y ácido linoleico (3,55%), en promedio; sin diferencia significativa entre el uso de n-hexano y acetato de etilo. También se alcanzó un alto valor de ácido linolénico (49,10% promedio), siendo mayor en la muestra extraída con acetato de etilo. En conclusión, el acetato de etilo puede sustituir al n-hexano como solvente en la extracción de aceite de semillas de sacha inchi y brindar un menor impacto ambiental, mayor seguridad y mejor calidad.
Keywords: SACHA INCHI; ACIDOS GRASOS POLIINSATURADOS; ACETATO DE ETILO; N-HEXANO